Stages of Research and Development Model Research and Development (R&D) - Torang Siregar (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
One of the efforts that every educational person can make to improve the quality of education in Indonesia is research, especially educational research. Through research, problems in education can be identified and then solutions can be found. New, more innovative things in education can also be developed and applied from research. There are several types of research that can be carried out, one of which is research and development (R&D). Initially, research and development was applied to the industrial world, and was the spearhead of an industry in producing new products needed by the market. Almost 4% of costs are used for this research, even for certain fields such as computers and pharmaceuticals the cost allocation can exceed 4% (Borg and Gall, 1989). Meanwhile, in the social and educational fields, the role of research and development is still very small, namely less than 1% of overall education costs. This is considered to be one of the main reasons why progress in education lags somewhat behind when compared to other fields. As stated by Borg and Gall (1989), unfortunately, R & D still plays a minor role in education. Less than one percent of education expenditures are for this purpose. This is probably one of the main reasons why progress in education has been logged for behind progress in other fields.